Description of Evandromyia (Aldamyia) orcyi, a new phlebotomine species (Diptera: Psychodidae: Phlebotominae) from the State of Mato Grosso do Sul, Brazil - Alessandra Gutierrez de Oliveira; Cristiani de Castilho Sanguinette; Paulo Silva de Almeida; José Dilermando Andrade Filho (Parasites & Vectors, 2015)
Abstract Background The genus Evandromyia is widely found in Brazil, but occurs mainly in Brazilian savannah. To date 13 species have been described in the subgenus Aldamyia. Here we described a new species of Evandromyia (Aldamyia) collected in the State of Mato Grosso do Sul, Brazil. Methods Measurements were made using a micrometer eyepiece on an Olympus CH-2 binocular microscope and drawings were executed with the aid of a camera lucida. Results The new species, Evandromyia orcyi sp. nov., is closely related to Evandromyia lenti, Evandromyia carmelinoi and Evandromyia evandroi, however, characteristics of the male terminalia and female spermathecae distinguish it from other species of the genus Evandromyia. Conclusion With the description of Evandromyia orcyi sp. nov., six species of the subgenus Aldamyia have been reported from the State of Mato Grosso do Sul.